Embryonic and early larval development of seven-line barb (Probarbus jullieni sauvage 1880) and lemon fin barb hybrid (Hypsibarbus wetmorei smith 1931 x Barbonymus gonionotus bleeker 1849) - Zakaria, Mohd Hazmadi (2015)
Embryonic and larval development of Temoleh, Probarbus jullieni and hybrid of Kerai ♂ (Hypsibarbus wetmorei) X Lampam Jawa ♀ (Barbonymus gonionotus) were investigated under laboratory condition. The matured eggs and sperms were collected by stripping each of the brood stocks species. Temoleh eggs were fertilized with a diluted concentration of normal milt of the same species while eggs of Lampam Jawa were fertilized with sperm of Kerai in two different experiments. The embryonic developing stages were observed in stages, beginning every 10 min intervals for the first hour, 20 min intervals at the second hour, 30 min for the next hour and then hourly intervals up to hatching. When hatching was completed, the observations were continued at 2-hour interval for the first day and at least every 6-hour interval for the following days. In P. jullieni, hatching started at 22-hour post-fertilization and fully completed within 25-hour at temperature ranged from 26.0 to 28.0 ºC. The hatching of Kerai hybrid occurred at 14-hour after fertilization at temperature ranged from 23.0 to 25.0 ºC. The yolk sac of the early larval development of P. jullieni was completely absorbed after 61-hour of hatching and the larvae started to swim actively and fed exogenously. The larvae of Kerai hybrid swam actively when the yolk sac became absent at 46-hour after hatching, and completed its early larval development. This study represents the first time description of the early development stages for P.jullieni and the hybrid of H. wetmorei ♂ X B. gonionotus ♀ in captive breeding condition. The valuable knowledge and information emerged from this designated studies will ultimately be useful towards understanding the reproductive biology of the two freshwater fishes. It will specifically enhance knowledge on seed production and larval rearing of the endangered P. jullieni and Kerai hybrid for aquaculture purpose.